THE INFLUENCE OF THE UTILIZATION OF DIGITAL LIBRARY ON THE MOTIVATION AND ACCOUNTING LEARNING OUTCOMES OF VOCATIONAL SMK LABOR BINAAN FKIP UNRI PEKANBARU - Desty Auliani Zulkarnain; Gimin; Hendripides (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study aims to determine: (1) Is there an effect of the use of the school's digital library on the learning motivation of the FKIP UNRI FKIP-assisted SMK students 'accounting skills program, (2) Is there an effect of the use of the school's digital library on the learning outcomes of the FKIP-assisted SMK students' accounting skills program. UNRI, (3) Is there an effect of the use of digital libraries and learning motivation on the learning outcomes of the accounting skills program of FKIP UNRI Fostered Vocational School students.This research method uses descriptive quantitative research. The population in this study were students of class X Accounting 2 at Vocational High School of FKIP, Riau University Pekanbaru, by taking a sample of the entire population as many as 26 students. Collecting data using questionnaires and documentation, data analysis using descriptive analysis and regression analysis.The results of the study state that: (1) The use of digital libraries partially affects the motivation to learn business economics in class 10 accounting students at SMK Labor Assisted by FKIP UNRI Pekanbaru. Where the motivation to learn business economics is influenced by the use of digital libraries of 91.9%. (2) The use of digital libraries partially has no effect on the learning outcomes of business economics for class 10 accounting students at SMK Labor Assisted by FKIP UNRI Pekanbaru. Where learning outcomes are influenced by the use of digital libraries by 10%. (3) The simultaneous use of digital libraries has an effect on learning motivation, while the simultaneous use of digital libraries has no effect on the learning outcomes of business economy class X Accounting 2 at SMK Labor Assisted by FKIP UNRI Pekanbaru.